Optimization of Extract Concentration and Polyvinyl Pirolidon Binding Material on Granule Red Betel Leaves Extract (Piper crocatum Ruiz & Pav) as Antihyperuricemic - Dian Ratih Laksmitawati; Liliek Nurhidayati; Mochamad Futuchul Arifin; Bagus Bahtiar (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Ethanolic extract of red betel leaves (Piper crocatum Ruiz & Pav) has antihyperuricemic activity. In order to be applicable to consume, this extract need to be formulated into pharmaceutical dosage form. Granules which is packed in a tea sac bag was considered to be more practical andappropriate for person suff ering hyperuricemic, because they have to drink more water. In the granulation process, the he binder plays an important role so that this study aims to fi nd the optimal red betel leaf granule formula with variation on the extract dose and the polyvinyl pyrolidone (PVP) binder and prove granule activity in vivo in mouse hyperuricemia model. The extract was prepared by macerationthe leaves in 96% ethanol and sprayed dried by hot air. The powder was then formulated to granules form in 22 factorial design. The factors were the extract dosages (38% dan 47.51%) dan the amount of PVP (Polyvinyl Pyrrolidone) as a binder (0.5% dan 2%). The physical and chemical properties of the granules were evaluated, interaction dosage, PVP concentration and each properties was analysed by making the contour plot and superimposed contour plot to get the optimum formula. The in vivo antihyperuricemic activity of the granules was determined in hyperuricemic mice. The result showed that the optimum formula was found in granules that contained 42.5% extract and 1% PVP. At the equivalent dosage of 455 mg extract/kg, this granules formula had antihyperuricemic activity decreasing 54.2 %plasma uric acid level significantly. Thus it can be concluded that the optimum granules of ethanol extract of red betelleaf with 42.5% extra ct content and 1% PVP proved to have antihiperurisemia activity in mice induced by chicken extractand potassium oxonate.